Therapeutic effect of CTLA4-Ig on a murine model of primary biliary cirrhosis - Dhirapong, Amy (2013)
Collectively, the data in both humans and murine models of human primary biliary cirrhosis (PBC) suggest that activated T cells, particularly CD8 T cells, play a critical role in biliary cell destruction. Under physiological conditions, T cell activation involves two critical signals that involve the MHC and a set of co-stimulatory molecules which include a receptor on T cells coined cytotoxic T lymphocyte antigen 4 (CTLA-4). Germane to the studies reported herein, signaling via CTLA-4 has the potential to modulate co-stimulation and induce inhibitory signals. In this study we have taken advantage of our well-defined murine model of PBC in which mice are immunized with 2-octynoic acid coupled to BSA, leading to the production of high titer anti-mitochondrial autoantibodies and portal cellular infiltrates. To investigate the potential of CTLA-4 Ig as an immunotherapeutic agent, we treated mice both before and after induction of autoimmune cholangitis. Firstly, we demonstrate that CTLA-4 Ig treatment begun one day before 2-OA-BSA immunization, completely inhibits the manifestations of cholangitis, including AMA production, intra-hepatic T cell infiltrates and bile duct damage. However, and more critically, treatment with CTLA-4 Ig initiated after the development of autoimmune cholangitis in previously immunized mice, also resulted in significant therapeutic benefit, including reduced intra-hepatic T cell infiltrates and biliary cell damage, although AMA levels were not altered. These data suggest that an optimized regimen with CTLA-4 Ig has the potential to serve as an investigative therapeutic tool in patients with PBC.